1979
DOI: 10.1139/e79-068
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the tectonic history of the Innuitian Province, Arctic Canada

Abstract: The Innuitian Tectonic Province contains the record of a Phanerozoic mobile belt in northern Greenland and the Canadian Arctic Archipelago. Two fundamentally different phases in its development were separated by the Devonian–Carboniferous Ellesmerian Orogeny. The first contribution focuses on the early Paleozoic history of a key area, the second summarizes the Carboniferous to Cenozoic history of most of the Canadian part of the province.(1) The early Paleozoic architecture of the mobile belt is apparent only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…8). A diamictite has locally been described and has been correlated with other Vendian tilloids (Trettin and Balkwill, 1979). A silicic tuff in the upper part of the succession (Milne Fiord Assemblage: Fig.…”
Section: Regional Tectonostratigraphic Correlationmentioning
confidence: 87%
See 1 more Smart Citation
“…8). A diamictite has locally been described and has been correlated with other Vendian tilloids (Trettin and Balkwill, 1979). A silicic tuff in the upper part of the succession (Milne Fiord Assemblage: Fig.…”
Section: Regional Tectonostratigraphic Correlationmentioning
confidence: 87%
“…7). A large stratigraphic hiatus occurs from the Late Devonian to the Mississippian and correlates with the Ellesmerian Orogeny (Trettin and Balkwill, 1979;Christie, 1979;Dawes and Peel, 1981). Trettin (1987) suggested that juxtaposition of the Pearyan terrane and the Hazen basin occurred in the Ludlow.…”
Section: Regional Tectonostratigraphic Correlationmentioning
confidence: 97%
“…[31,53,55,56,66,67,69]). The dominant structures are large-scale anticlines and synclines [41,53], which are exposed on Melville Island, Bathurst Island, and Ellesmere Island.…”
Section: Ellesmerian Fold-and-thrust Beltmentioning
confidence: 99%
“…The regional geology of the Arctic Islands has been established during the last 30 years by the Geological Survey of Canada (Thorsteinsson and Tozer 1970;Trettin and Balkwill 1979;Trettin, in press). Three tectono-stratigraphic sequences, separated by major unconformities, are mapped on the land areas adjacent to the northern portion of the polar continental shelf (Fig.…”
Section: Geological Settingmentioning
confidence: 99%